Total focusing method with correlation processing of antenna array signals; IOP Conference Series: Materials Science and Engineering; Vol. 327 : Mechanical Engineering, Automation and Control Systems (MEACS 2017) - Kozhemyak O. A. Olesya Anatolievna; Bortalevich S. I.; Loginov E. L.; Shinyakov Y. A.; Sukhorukov M. P. (Simulation and automation of production engeenering, 2018)
Title screen